The Health Literacy of Adults in Alborz Province in Iran - Seddigheh Ravati; Malihe Farid (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: Health literacy is defined as the ability of an individual to acquire, interpret, and understand the basic information about health services and to use them. Health literacy is a strong predictor of health. Its low level is germane to health problems of people and society as well as economic costs. This study was designed to determine the level of health literacy considering socio-demographic factors in residents of Alborz province in 2015. Methods: This is a cross-sectional study in which 465 people aged between 18 and 60 years old living in Alborz province were evaluated using two-stage random sampling technique (stratified and cluster sampling). In this study, Iranian Health Literacy Questionnaire (IHLQ) and socio-demographic Information Questionnaire were used to collect the required data. The data were analyzed using descriptive statistics as well as T-test, Mann-Whitney test, and Spearman correlation test using SPSS software. Results: The mean age of participants was 36.57(±11.08) years old and 68.2% of them were female. 22.4% of people had adequate, 44.3% had a moderate, and 33.3% had a poor level of health literacy. Health literacy in all dimensions of IHLQ except individual empowerment and social empowerment was moderate. People's access to health information also was moderate. The T-test indicated that the health literacy score was significantly higher in the individuals with the educational level of diploma and higher (p= 0.000), in Persian people (p= 0.008), and in unemployed people (p= 0.006). Conclusion: The high level of inadequate (moderate and poor) health literacy of 77.6% of the Alborz province population should be taken into consideration in health system policies to apply an effective strategy for  promoting  health literacy that results in better health status, regarding effective socio-demographic factors for each dimension of health literacy.